Study to Assess the Effectiveness of Teaching Program on Knowledge Regarding Management of Patients with Regenerative Orthopedics Procedures Among Orthopedic Nurses at Selected Orthopedic Departments - V.G. Veeresh; Sujata Japannavar (International Journal of Orthopedic Nursing and Practices, 2025)
Regenerative therapy is an emerging treatment approach in medical science. It focuses on the use of stem cell therapy, biological treatments, tissue engineering, platelet-rich plasma, prolotherapy, and nutraceutical supplements to replace or restore dysfunctional structures or organs. Regenerative therapy emphasizes the body’s natural healing process; it supports physiological healing mechanisms and repairs damaged tissues. It is a minimally invasive approach with expanding applications across various medical fields, including surgery, degenerative disorders, interventional procedures, and orthopedic management. Regenerative orthopedics refers to the application of regenerative therapy in the management of musculoskeletal diseases and disorders. The role of orthopedic nurses in caring for patients undergoing regenerative treatment is crucial; however, studies indicate that nurses working in orthopedic departments often have inadequate knowledge of regenerative orthopedic management. Hence, the present study aimed to assess the knowledge of orthopedic nurses regarding regenerative orthopedic procedures and to improve their knowledge in the management of musculoskeletal diseases. A one-group pretest–posttest design was adopted for the study, involving 60 orthopedic nurses working in the orthopedic department of a selected hospital. Participants were selected using a purposive sampling technique based on inclusion criteria. A structured knowledge questionnaire was developed, which demonstrated a content validity index of 0.89 and a reliability coefficient of 0.91 as validated by experts. The questionnaire was administered as a pretest to assess baseline knowledge, followed by the implementation of a teaching program. After one month, a posttest was conducted using the same questionnaire. The collected data were analyzed using SPSS version 16.0 software. The results revealed that the baseline knowledge level of orthopedic nurses was poor. The teaching program was found to be effective in significantly improving the knowledge level of orthopedic nurses (p ≤ 0.001). The study concluded that continuing education programs are essential for nurses to enhance effective clinical practice and ensure quality orthopedic care.
Keywords: continuing education program; knowledge assessment; musculoskeletal disorders; orthopedic nurses; regenerative therapy